Land-use suitability zoning model for productive alternatives of the municipality of Rivera, Huila (Colombia) - Tamayo Quimbaya, Constanza Paola; Muñoz Velasco, Luis Alfredo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This article presents a zoning model of the suitability of the rural agricultural land of the municipality of Rivera, and identifies the areas with the greatest productive and socioeconomic potential in the region. In this context and having as a reference the agroecological conditions categorized as high, medium, and low, as well as geographic positioning and access to primary routes of the productive and social territorial offer of the rural property, the producing community, with the leadership and technical support of the Secretariat of Agriculture and Mining of the Governor’s Office of Huila and the Rural Agricultural Planning Unit (UPRA) identified 22 productive alternatives in various workshops developed in the territory, in which we were active witnesses. These alternatives were in line with global standards for the department; however, 12 were prioritized, and this work refers to 10 productive alternatives only due to the ease of access to cartographic and statistical information. The methodology designed by UPRA for rural and social productive ordering, the tools contained in the Corine Land Cover methodology and the ArcGIS software were used for the analysis.